2010
DOI: 10.1007/s10811-010-9576-9
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of an extracellular alginate lyase from Aspergillus oryzae isolated from brown seaweed

Abstract: The extracellular enzyme alginate lyase produced from marine fungus Aspergillus oryzae isolated from brown alga Dictyota dichotoma was purified, partially characterized, and evaluated for its sodium alginate depolymerization abilities. The enzyme characterization studies have revealed that alginate lyase consisted of two polypeptides with about 45 and 50 kDa each on 10% sodium dodecyl sulfate polyacrylamide gel electrophoresis and showed 140-fold higher activity than crude enzyme under optimized pH (6.5) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…A double bond is then formed between nonreducing ends, namely C4 and C5, where the glycosidic bond is located, and an oligomeric oligosaccharide with a 4‐deoxy‐L‐erythro‐hex‐4‐enepyranosyluronate structure is simultaneously produced (Wong, Preston, & Schiller, ). Alginate lyases can be obtained from various sources, such as marine and terrestrial bacteria (Yu, Zhu, Wang, Tan, & Yin, ; Zhu, Ni, Sun, & Yao, ), fungus (Cao et al, ; Singh et al, ), virus (Ichiro et al, ), marine mollusks (Hata et al, ; Rahman, Inoue, Tanaka, & Ojima, ), and algae (Inoue et al, ). They can be classified into two groups, namely, polyG specific (polyG lyase, EC 4.2.2.11) and polyM specific (polyM lyase, EC 4.2.2.3), because of their different effects on substrates (Zhu & Yin, ).…”
Section: Introductionmentioning
confidence: 99%
“…A double bond is then formed between nonreducing ends, namely C4 and C5, where the glycosidic bond is located, and an oligomeric oligosaccharide with a 4‐deoxy‐L‐erythro‐hex‐4‐enepyranosyluronate structure is simultaneously produced (Wong, Preston, & Schiller, ). Alginate lyases can be obtained from various sources, such as marine and terrestrial bacteria (Yu, Zhu, Wang, Tan, & Yin, ; Zhu, Ni, Sun, & Yao, ), fungus (Cao et al, ; Singh et al, ), virus (Ichiro et al, ), marine mollusks (Hata et al, ; Rahman, Inoue, Tanaka, & Ojima, ), and algae (Inoue et al, ). They can be classified into two groups, namely, polyG specific (polyG lyase, EC 4.2.2.11) and polyM specific (polyM lyase, EC 4.2.2.3), because of their different effects on substrates (Zhu & Yin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The alginate lyases found in Pseudoalteromonas sp. SM0524 , Aspergillus oryzae , and Vibrio sp. YKW‐34 were preferable to hydrolyze poly (M) than poly (G).…”
Section: Resultsmentioning
confidence: 99%
“…The K m and V max values of the purified enzyme were found to be 1.07 mg alginate/ml and 128.2 U/mg protein. K m and V max values of alginate lyase from Aspergillus oryzae were 21.52 mg/ml and 222.68 U/mg proteins, respectively [21]. Several reports indicated that the optimum activity of alginate lyase was obtained between pH 7.0 and 8.0 from, Streptomyces species A5, and Microbulbifer sp.…”
Section: Discussionmentioning
confidence: 98%
“…Alginate lyase from Pseudomonas stutzeri MSEA04 can be considered more thermostable than the alginate lyase produced from Escherichia coli, which lost 50% of its activity after 10 min at 45 °C [14], and alginate lyase obtained from Aspergillus oryzae which lost completely its activity at 50 °C [21]. However, it was still considered to be less stable than the alginate lyase obtained from Bacillus species which retained 60% and 50% of its activity after treatment for 30 min at 20 °C and 60 °C, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation